2020
DOI: 10.1177/0194599820966622
|View full text |Cite
|
Sign up to set email alerts
|

Airway Hemangiomas in PHACE Syndrome: A Multicenter Experience

Abstract: Objective To describe the prevalence and clinical characteristics of airway findings in a multi-institutional cohort of PHACE patients. Study Design Multicenter retrospective case series. Setting Multidisciplinary vascular anomalies clinics at 2 institutions. Methods Data were collected from the electronic medical record, including clinical presentation, airway findings, treatment, and outcomes. Results Of 55 PHACE patients, 22 (40%) had airway hemangiomas. Patients with airway involvement were more commonly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Furthermore, the PI3K/AKT pathway has been demonstrated to suppress hemangioma proliferation by downregulating the expression of proliferating cell nuclear antigen, which may further influence the progression of hemangioma ( 42 ). In the present study, it was found that the PI3K/AKT signaling pathway was regulated by miR-203a-3p in hemangioma, which was in line with the data previously reported in other tumors, such as renal cell carcinoma, papillary thyroid cancer and glioblastoma ( 10 , 43 , 44 ). In addition, it was confirmed that miR-203a-3p can directly suppress VEGFA expression and the PI3K/AKT pathway, which could suppress the proliferation of hemangioma, thereby uncovering the miR-203a-3pVEGFA/PI3K/AKT axis.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the PI3K/AKT pathway has been demonstrated to suppress hemangioma proliferation by downregulating the expression of proliferating cell nuclear antigen, which may further influence the progression of hemangioma ( 42 ). In the present study, it was found that the PI3K/AKT signaling pathway was regulated by miR-203a-3p in hemangioma, which was in line with the data previously reported in other tumors, such as renal cell carcinoma, papillary thyroid cancer and glioblastoma ( 10 , 43 , 44 ). In addition, it was confirmed that miR-203a-3p can directly suppress VEGFA expression and the PI3K/AKT pathway, which could suppress the proliferation of hemangioma, thereby uncovering the miR-203a-3pVEGFA/PI3K/AKT axis.…”
Section: Discussionsupporting
confidence: 93%
“…Only two out of 10 patients with large segmental IH of the face were diagnosed with PHACES syndrome compared to a higher percentage in literature data (47%) (4,6). When PHACES syndrome is suspected, it is necessary to perform a full workup, including cardiologic, ophthalmologic, and neurologic investigation with appropriate imaging (19).…”
Section: Discussionmentioning
confidence: 94%
“…PHACES syndrome is characterized by posterior fossa anomalies, IH, aortic, cardiac, and eye malformations, and sternal defect. Several studies reported its association with AIHs with variable percentages (16-50%) (4)(5)(6). AIHs usually involve the subglottis, which is the narrowest part of the pediatric airway and are mostly located in its left posterolateral part (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…10 Airway hemangioma has been cited to be anywhere from 40% to 52% in the PHACE syndrome population. 9,11 Although the incidence of airway hemangiomas in general is well known in patients with PHACE syndrome, the incidence of specifically subglottic hemangioma in PHACE syndrome has not yet been described. Additionally, children with PHACE Syndrome also potentially have a poor response to propranolol, which is first line medical treatment and increased rebound growth after treatment completion which should be considered when these patients present with airway IH.…”
Section: Discussionmentioning
confidence: 99%